Development of control mechanisms for a laser wakefield accelerator-driven bremsstrahlung x-ray source for advanced radiographic imaging. (29th October 2020) - Underwood, C I D; Baird, C D; Murphy, C D; Armstrong, C D; Thornton, C; Finlay, O J; Streeter, M J V; Selwood, M P; Brierley, N; Cipiccia, S; Gruse, J-N; McKenna, P; et al.
Abstract: A high power laser was used to accelerate electrons in a laser-driven wakefield accelerator. The high energy electrons were then used to generate an x-ray beam by passing them through a converter target. This bremsstrahlung source was characterised and used to perform penetrative imaging of industrially relevant samples. The photon spectrum had a critical energy in excess of 100 MeV and a source size smaller than the resolution of the diagnostic ( ≲ 150 µ m). Simulations indicate a significantly smaller source is achievable. Variations in the x-ray source characteristics were realised through changes to the plasma and converter parameters while simulations confirm the adaptability of the source. Imaging of high areal density objects with 150 µ m resolution was performed, demonstrating the unique advantages of this novel source.